Tourism and Culture in the Age of Innovation Second International Conference IACuDiT, Athens 2015 - Katsoni, Vicky; Stratigea, Anastasia (Springer Proceedings in Business and Economics, 2016)
This book focuses on cultural tourism as it develops into the second decade of the new millennium. It presents recent hospitality and tourism research findings from various sources, including academic researchers and scholars, industry professionals, government and quasi-government officials, and other key industry practitioners. It discusses the latest tourism industry trends and identifies gaps in the research from a pragmatic and applied perspective. It includes specific chapters on innovation in tourism, the virtual visitor, cross-cultural visions of digital collections, heritage and museum management in the digital era, cultural and digital tourism policy, marketing and governance, social media, emerging technologies and e-tourism and many other topics of contemporary significance in global hospitality and tourism. The book is edited in collaboration with the International Association of Cultural and Digital Tourism (IACuDiT) and includes the proceedings of the Second International Conference on Cultural and Digital Tourism.